Integrated Clinical Decision Support Systems Promote Absolute Cardiovascular Risk Assessment: An Important Primary Prevention Measure in Aboriginal and Torres Strait Islander Primary Health Care - Matthews, Veronica; Burgess, Christopher P.; Connors, Christine; Moore, Elizabeth; Peiris, David; Scrimgeour, David; Thompson, Sandra C.; Larkins, Sarah; Bailie, Ross (Frontiers in Public Health, 2017)
Background: Aboriginal and Torres Strait Islander Australians experience a greater burden of disease compared to non-Indigenous Australians. Around one-fifth of the health disparity is caused by cardiovascular disease (CVD). Despite the importance of absolute cardiovascular risk assessment (CVRA) as a screening and early intervention tool, few studies have reported its use within the Australian Indigenous primary health care (PHC) sector. This study utilises data from a large-scale quality improvement program to examine variation in documented CVRA as a primary prevention strategy for individuals without prior CVD across four Australian jurisdictions. We also examine the proportion with elevated risk and follow-up actions recorded. Methods: We undertook cross-sectional analysis of 2,052 client records from 97 PHC centres to assess CVRA in Indigenous adults aged ≥20 years with no recorded chronic disease diagnosis (2012–2014). Multilevel regression was used to quantify the variation in CVRA attributable to health centre and client level factors. The main outcome measure was the proportion of eligible adults who had CVRA recorded. Secondary outcomes were the proportion of clients with elevated risk that had follow-up actions recorded. Results: Approximately 23% (n=478) of eligible clients had documented CVRA. Almost all assessments (99%) were conducted in the Northern Territory. Within this jurisdiction, there was wide variation between centres in the proportion of clients with documented CVRA (median 38%; range 0-86%). Regression analysis showed health centre factors accounted for 48% of the variation. Centres with integrated clinical decision support systems were more likely to document CVRA (OR 21.1;95%CI 5.4-82.4;p<0.001). Eleven percent (n=53) of clients were found with moderate/high CVD risk, of which almost one third were under 35 years (n=16). Documentation of follow-up varied with respect to the targeted risk factor. Fewer than 30% with abnormal blood lipid or glucose levels had follow-up management plans recorded. Conclusion: There was wide variation in CVRA between jurisdictions and between PHC centres. Learnings from successful interventions to educate and support centres in CVRA provision should be shared with stakeholders more widely. Where risk has been identified, further improvement in follow-up management is required to prevent CVD onset and reduce future burden in Australia’s Indigenous population.